Deindustrialization and the Moral Economy of the Scottish Coalfields, 1947 to 1991. (7th January 2014) - Phillips, Jim
Abstract The long-running deindustrialization in the Scottish coalfields, the consequence of political decisions, took place in three distinct periods analyzed here: "restructuring, " 1958–1967, when, in response to union activism, a large number of closures was offset by government and industry initiatives to provide or stimulate alternative employment; "stabilization, " 1968–1977, when closures were minimized as the broader industrial economy slowed; and then "accelerated contraction, " 1978–1987, within the larger program of economic restructuring engineered by Margaret Thatcher's Conservative UK governments. Moral economy arguments shaped the debate about deindustrialization in the first two phases: closures were legitimate only where agreed to by the workforce, who would in turn receive guaranteed economic security. These factors did not apply in the final phase, when closures were enforced and redundant miners had limited employment alternatives.